Dynamic Reliability Evaluation of Road Vehicle Subjected to Turbulent Crosswinds Based on Monte Carlo Simulation. (29th January 2017) - Wang, Bin; Li, Yongle; Yu, Helu; Liao, Haili
Abstract : As a vehicle moves on roads, a complex vibration system of the running vehicle is formed under the collective excitations of random crosswinds and road surface roughness, together with the artificial handing by the drivers. Several numerical models in deterministic way to assess the safety of running road vehicles under crosswinds were proposed. Actually, the natural wind is a random process in time domain due to turbulence, and the surface roughness of a road is also a random process but in spatial domain. The nature of a running vehicle therefore is an extension of dynamic reliability excited by random processes. This study tries to explore the dynamic reliability of a road vehicle subjected to turbulent crosswinds. Based on a nonlinear vibration system, the dynamic responses of a road vehicle are simulated to obtain the dynamic reliability. Monte Carlo Simulation with Latin Hypercube Sampling is then applied on the possible random variables including the vehicle weight, road friction coefficient, and driver parameter to look at their effects. Finally, a distribution model of the dynamic reliability and a corresponding index for the wind-induced vehicle accident considering these random processes and variables is proposed and employed to evaluate the safety of the running vehicle.